Título Padrão - Alcântara Alves, Leonardo; Kaiser, Jackson Pereira de Sousa (Revista Labor, 2020)
Commonly used in academic productions, the content analysis of documents is the result of an effort by the researcher to find records, facts, speeches or other items that can contribute to his research. This paper presents an analysis of the IFRN's Pedagogical Political Project (PPP), which allows the obtainment of basic foundations of pedagogical and teaching practices for the construction of Scientific Literacy (SL) skills in students. The content analysis was based on Bardin (2011). The results obtained dialogue with authors who discuss SL, such as Santos (2007) and Norris and Phillips (2003) and the factors that must be taken into account for their construction. In addition, it is possible to verify the presence of elements in the document that guide the development of the SL. It is hoped that this work can help teachers who reflect their practice and who seek institutional documents for instruments to improve teaching practice.